Efficacy and Resistance of Afatinib in Chinese Non-Small Cell Lung Cancer Patients With HER2 Alterations: A Multicenter Retrospective Study - Song, Zhengbo; Lv, Dongqing; Chen, Shiqing; Huang, Jianhui; Wang, Liping; Xu, Shuguang; Chen, Huafei; Wang, Guoqiang; Lin, Quan (Frontiers in Oncology, 2021)
Background Non-small cell lung cancer (NSCLC) patients with HER2 mutations and amplification may benefit from HER2-targeted therapy, including afatinib. However, the data regarding the clinical activity of afatinib in Chinese patients with NSCLC harboring HER2 alterations are limited. Patients and methods We retrospectively included metastatic NSCLC patients harboring HER2 alterations who treated with afatinib. The clinical outcomes included overall response rate (ORR), progression-free survival (PFS) and overall survival (OS). The genomic profiling data after progression on afatinib were analyzed. Results We included 54 patients harboring HER2 mutations and 12 patients harboring HER2 amplification. The ORR was 24% (95% CI, 16–36%), the median PFS was 3.3 months (95% CI, 2.2–4.4), and the median OS was 13.9 months (95% CI, 11.4–16.5). Patients with HER2 exon 20 mutations had numerically worse ORR (17% vs 42%), shorter PFS (2.6 vs 5.8 months, HR, 2.5; 95% CI, 1.2–5.5; P = 0.015) and OS (12.9 vs 33.3 months, HR, 4.4; 95% CI, 1.3–14.8; P = 0.009) than patients with other mutations. For HER2-amplified patients, the ORR was 33% (95% CI, 14–61%), the median PFS was 3.3 months (95% CI, 2.6–4.0), and the median OS was 13.4 months (95% CI, 0–27.6). The most frequently mutated genes in afatinib-resistant patients were TP53 (44%) and EGFR (33%). Three afatinib-resistant patients harbored secondary HER2 alterations. Conclusions Our results suggest that afatinib has a promising anti-tumor activity in patients with NSCLC harboring HER2 alterations. To our knowledge, this is the largest retrospective study about the clinical activity of afatinib in NSCLC patients with HER2 alterations.